Multidisciplinary Perspectives on Islamic higher Education Curriculum Orientation in Independent Campus Policy (Program Studi Pendidikan Agama Islam, 2021)
Curriculum has strategic values in the era of independent campus. This research aims to construct a curriculum based multiple perspectives tends to learners’ preference and diversity in Islamic Higher Education. It’s a mix-method research. Qualitative methods, using naturalistic design with interactive models, while quantitative methods with cross-sectional surveys to determine the level of stakeholder’s understandings and the result of it. The result found that multiple dimensions leads to an eternal-essential closed to the Oneness of God, creativity, capability. The other one refers to instrument; model, knowledge, organization, sequence, need analysis, purpose, value, and stakeholder. Furthermore, the appropriate one tends to an essential-humanistic technologies curriculum in fulfilling for independent campus recognition.